“El efecto impositivo del impuesto a la renta en los productores bajo el régimen emprendedor en Cotopaxi. periodo 2022”. - Valverde Gallo, Carlos Alexander (2024)
The research project analyzes the problems and effects generated by implementing the RIMPE Entrepreneur Regime and its methodology for calculating income tax on producers operating under this Regime in the Province of Cotopaxi during the fiscal year 2022. The research analyses how this tax affects producers, their reinvestment capacity, and the obstacles associated with compliance with tax obligations. It contextualizes the tax situation in Ecuador, highlighting the implementation of the Régimen Impositivo para Emprendedores y Negocios Populares RIMPE (Tax Regime for Entrepreneurs and Popular Businesses), where the authorities reported on the economic problems arising from the COVID-19 pandemic. The 77,998 beneficiaries of the project include Cotopaxi producers under the RIMPE Entrepreneur regime and citizens with or without RUC. The project is based on the RIMPE Entrepreneurial Regime's legal framework, detailing the taxpayer's formal duties and discussing the technical aspects of income tax. The methodology is described, which combines quantitative approaches as well as the application of surveys to a representative sample of producers and accountants to obtain the information that will later be contrasted through the analysis of the databases presented by the Internal Revenue Service on its website, to understand and compare the information from the government's perspective and the reality of the producer sector under the RIMPE Entrepreneur Regime, the tax burden of the income tax shows a higher tax burden because this type of taxpayers cannot consider the expenses related to their economic activity according to what is determined by the regulations, a different way of determining the taxable base for the calculation of income tax is constituted, encouraging taxpayers to be within this Regime.